Analisis Perbedaan Strategi Pembelajaran Guru pada Kurikulum Merdeka dan Kurikulum 2013 - Rosmawaty Rosmawaty; Dwi Tiara Gustiani; Nazwa Dafina; Silfania Cahya Andjani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the differences in teachers' learning strategies between the Merdeka Curriculum and the 2013 Curriculum based on a review of recent and relevant scientific literature. The curriculum transition from the 2013 Curriculum to the Merdeka Curriculum carries significant implications for how teachers plan, implement, and evaluate learning. The method used is a qualitative approach with a library research design. Data sources include scientific journal articles, policy documents, and reference books published between 2019 and 2025. Data analysis was conducted descriptively and comparatively. The findings indicate that learning strategies in the 2013 Curriculum are systematic and structured through Core Competencies and Basic Competencies (KD), while the Merdeka Curriculum provides greater flexibility through Learning Outcomes (C) Learning Objectives (TP), and the Learning Objective Flow (ATP). Fundamental differences are evident in the planning, implementation, and evaluation of learning. The Merdeka Curriculum promotes more innovative, contextual, and student-centered learning, whereas the 2013 Curriculum tends to be more rigid and administrative in its implementation. The success of learning strategy implementation in both curricula depends beavily on teachers' pedagogical competence and readiness to adapt to curricular changes.